Bond market analysis: the main constraints in the research of 21st century - Jasienė, Meilė; Paškevičius, Arvydas; Astrauskaitė, Ieva (Business, Management and Economics Engineering, 2013)
Searching for alternative source of bank financing, the view on capital market is taken. Recent research on capital market issues are arranged into four dimensions: theory and assumptions of efficient capital market, government’s role in it, other distortions and global interrelatedness. Main investigations are decentralized and visualized in “theoretical eight” model. Conclusions made on the diversity of interpretation of market efficiency, strongly expressed demand of information symmetry, soft actions of governments and the value of foreign performance in domestic markets. Furthermore, new approach to the classification of countries by their maturity in capital market is argued. The state of art of 2009-2012 of bond market and government debt is briefly described.